2020
DOI: 10.3390/nano10010130
|View full text |Cite
|
Sign up to set email alerts
|

Round Robin into Best Practices for the Determination of Indentation Size Effects

Abstract: The paper presents a statistical study of nanoindentation results obtained in seven European laboratories that have joined a round robin exercise to assess methods for the evaluation of indentation size effects. The study focuses on the characterization of ferritic/martensitic steels T91 and Eurofer97, envisaged as structural materials for nuclear fission and fusion applications, respectively. Depth-controlled single cycle measurements at various final indentation depths, force-controlled single cycle and forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This has been confirmed by AFM ( Figure 5 and Figure 6 ). The mismatch between observed and predicted strength data can largely be reconciled by the application of an elastic modulus correction (EMC) procedure [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been confirmed by AFM ( Figure 5 and Figure 6 ). The mismatch between observed and predicted strength data can largely be reconciled by the application of an elastic modulus correction (EMC) procedure [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…This has been accomplished by applying an elastic modulus correction (EMC). While in recent previous work the EMC served the correction of various sources of biases of data from multiple sources (round robin testing) [ 24 ], here it was specifically performed to account for changes in pile-up height induced by pre-deformation.…”
Section: Discussionmentioning
confidence: 99%
“…A question arises from this issue: if the wear rate changes for smaller particles, would there be a suitable hardness to express the worn surface? The answer is not simple once the size effect is present in the indentation event, called the indentation size effect (ISE) [41][42][43][44][45][46][47]. For example, Pintaude et al [48] showed that the indentation size observed in steel could change the (Hi/Hw) CRIT value.…”
Section: Particle Fragmentation and Size Effectsmentioning
confidence: 99%
“…In the reported studies, the materials were typically exposed to self-ion irradiations using a single ion energy varying from study to study from below 1 MeV (Clozel et al, 2020) to above 10 MeV (Song et al, 2020). As reported by Ruiz-Moreno et al (2020) in conclusion for a Round Robin test, simple comparison of NI results from different laboratories is, however, still problematic. Saleh et al (2016) studied the effect of energy variations of He ions (including ion energies of 1, 2 and 3 MeV) on the NI response of an austenitic stainless steel.…”
Section: Introductionmentioning
confidence: 99%